Produksi Silase Rumput Gajah dalam Kegiatan Pengabdian Masyarakat Desa Karangkemiri Kecamatan Karanganyar Kabupaten Kebumen - Aqil Adyatama; Raditya Nandhirabrata; Vian Dwi Chalisty; Nunur Nuraeni; Mugiarto Mugiarto (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The Karangkemiri Livestock Farmers Group (KTT) in Kebumen Regency faces critical challenges in providing livestock feed during the dry season. The scarcity of fresh forage has led to a reliance on commercial feed, which has burdened livestock farmers' economic well-being. The Karangkemiri Livestock Farmers Group (KTT) in Kebumen Regency faces critical challenges in providing livestock feed during the dry season, when forage productivity drops drastically by up to 60% (Ministry of Agriculture, 2023). The region's agricultural waste potential is abundant but underutilized, with corn straw reaching 12 tons per season and cassava pulp reaching 5 tons per week. Through a participatory approach based on community-based participatory research (CBPR), this activity is designed to build livestock farmers' independence in feed management. An active farmer-to-farmer engagement model was adopted to ensure the sustainability of the technology, with a target of reducing production costs by 50% through optimizing local raw materials. Initial evaluations indicate a potential 25% increase in livestock productivity if silage is implemented consistently. The purpose of this activity is as an active participation of Ma'arif Nahdlatul Ulama University Kebumen Faculty of Agriculture and Animal Husbandry Undergraduate Program of Animal Husbandry as a higher education institution to implement knowledge to be disseminated to the community in order to realize the obligations of the three pillars of higher education tridharma college namely teaching research and community service, especially to the affected community, namely the Karangkemiri Village Community, Karanganyar District, Kebumen Regency.